2011
DOI: 10.1371/journal.pone.0014504
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Long-term Intravenous Sodium Nitrite Infusion in Healthy Volunteers

Abstract: BackgroundInfusion of sodium nitrite could provide sustained therapeutic concentrations of nitric oxide (NO) for the treatment of a variety of vascular disorders. The study was developed to determine the safety and feasibility of prolonged sodium nitrite infusion.MethodologyHealthy volunteers, aged 21 to 60 years old, were candidates for the study performed at the National Institutes of Health (NIH; protocol 05-N-0075) between July 2007 and August 2008. All subjects provided written consent to participate.Twel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 50 publications
8
99
0
Order By: Relevance
“…Although surprising, these results are in fact in line with a previous study by Pluta et al, 36 who reported no changes in blood pressure during sodium nitrite infusions at even higher doses and reaching plasma levels similar or higher than the ones reported here. 36 Similar results showing absence of changes in peripheral blood pressure mediated by nitrite infusions were recently reported also by Omar et al 27 In this regard, although previous studies have clearly showed that nitrite infusions increase peripheral blood flow at plasma concentrations close to the physiological range, 26,35 it seems that nitrite-induced changes in blood pressure requires higher intravenous nitrite doses 35 or, as suggested by the current study, a different administration route. For example, Webb et al 14 reported changes in blood pressure 2 to 3 hours after oral ingestion of inorganic nitrate, when nitrate was cumulatively converted to nitrite by the enterosalivary pathway.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although surprising, these results are in fact in line with a previous study by Pluta et al, 36 who reported no changes in blood pressure during sodium nitrite infusions at even higher doses and reaching plasma levels similar or higher than the ones reported here. 36 Similar results showing absence of changes in peripheral blood pressure mediated by nitrite infusions were recently reported also by Omar et al 27 In this regard, although previous studies have clearly showed that nitrite infusions increase peripheral blood flow at plasma concentrations close to the physiological range, 26,35 it seems that nitrite-induced changes in blood pressure requires higher intravenous nitrite doses 35 or, as suggested by the current study, a different administration route. For example, Webb et al 14 reported changes in blood pressure 2 to 3 hours after oral ingestion of inorganic nitrate, when nitrate was cumulatively converted to nitrite by the enterosalivary pathway.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous studies demonstrating pH-dependent nonenzymatic NO formation from nitrite immediately on contact with the acidic gastric juice. 28,[35][36][37] We cannot fully exclude that NO itself can escape directly into the systemic circulation to affect blood pressure. However, considering the high reactivity of the NO radical, in particular with oxyhemoglobin, another more stable NO reaction product is a more likely candidate for exerting such systemic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the apparent lack of tolerance (Haas et al, 1999;Dejam et al, 2007) would be an additional advantage over organic nitrates (Sage et al, 2000). However sustained high dose nitrite infusion can cause methemoglobinemia and hemolysis (Pluta et al, 2011). To date there have been no large scale studies of nitrite infusion in heart failure.…”
Section: Mechanisms Of Nitrite-mediated Vasodilatationmentioning
confidence: 99%
“…Of interest, nitrate was used in very high doses (often for weeks) at the beginning of the last century as a diuretic (Butler & Feelisch, 2008). Recent studies by Pluta et al (2011) have investigated the safety and feasibility of long-term intravenous infusion of sodium nitrite in healthy subjects. The authors demonstrated that acute intravenous infusion of sodium nitrite was tolerated up to a maximum dose at 267 μg/kg/h, and that the dose-limiting toxicity was reached at 446 μg/kg/h.…”
Section: Potential Toxicity Of Nitrite and Nitratementioning
confidence: 99%